(untitled) (Management and Connections Journal, 2021)
Shadowing is an emerging research technique in management studies, based on the researcher’s actions as a shadow of an organization’s member. This study analyzes the practice of shadowing in the field of management. A systematic literature review was carried out in the Scopus database. 173 articles were identified and analyzed through qualitative content analysis. As a result, it was possible to understand the concept of shadowing, its application, the main scenarios studied, and its limitations. The results showed the growing interest of researchers in the use of this technique in the management area. It was also possible to elaborate an overview on the application of shadowing and its benefits since it allows the researcher to obtain a holistic understanding of the context and provide information on invisible aspects of people’s work.